2022
DOI: 10.18256/2237-7956.2022.v12i2.4496
|View full text |Cite
|
Sign up to set email alerts
|

Convergência ou disparidade? Explorando a divulgação de Responsabilidade Social Corporativa no Brasil e na França

Abstract: O estudo tem por objetivo investigar o nível de divulgação de Responsabilidade Social Corporativa (RSC) dos bancos brasileiros e franceses. É um estudo quantitativo e descritivo. Foram analisados 8 indicadores ambientais e 24 indicadores sociais das empresas atuantes no Brasil e França, durante os anos de 2015, 2016 e 2017. Os resultados apontaram que os bancos sediados na França possuem uma maior divulgação de responsabilidade social corporativa do que os bancos brasileiros. Os achados sugerem que dadas às co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
2
0
1
Order By: Relevance
“…Thus, the institutional environment may justify the existence of a different effect of CSR on competitive strategies (intangibility, internationalization, and innovation) and its subsequent impact on the competitiveness of companies in different countries. The study by Pinheiro et al (2022), for example, conducted a comparative analysis between Brazilian and French companies and identified there is greater disclosure of CSR by French companies, considering that there is greater social and regulatory pressure for the disclosure of CSR practices in the country. Thus, it is suggested that: H1a: Competitive strategies positively influence the competitiveness of Brazilian companies.…”
Section: Corporate Social Responsibility Moderates the Relationship B...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the institutional environment may justify the existence of a different effect of CSR on competitive strategies (intangibility, internationalization, and innovation) and its subsequent impact on the competitiveness of companies in different countries. The study by Pinheiro et al (2022), for example, conducted a comparative analysis between Brazilian and French companies and identified there is greater disclosure of CSR by French companies, considering that there is greater social and regulatory pressure for the disclosure of CSR practices in the country. Thus, it is suggested that: H1a: Competitive strategies positively influence the competitiveness of Brazilian companies.…”
Section: Corporate Social Responsibility Moderates the Relationship B...mentioning
confidence: 99%
“…These characteristics significantly affect several aspects of companies in the countries (Delmas, 2002), including the social and environmental practices adopted, and the study in different realities is relevant (Pinheiro et al, 2022). For , Brazil has an institutional environment in which society, companies, and government do not act towards CSR in a systemic and integrated way.…”
Section: Introductionmentioning
confidence: 99%
“…Diante do exposto, este estudo parte da seguinte pergunta de pesquisa: Essas características afetam sobremaneira vários aspectos das empresas dos países (Delmas, 2002), inclusive as práticas sociais e ambientais adotadas, sendo relevante o estudo em diferentes realidades (Pinheiro et al, 2022) (2014), a França é um país que se engaja em práticas sociais e ambientais desde a normatização de 1977, que exigia que as empresas francesas divulgassem informações sociais.…”
Section: Introductionunclassified